Preparation method and application of hydrophobic alumina nanoporous coating with added antiscalant
By introducing a scale inhibitor into the alumina nanotube layer prepared by anodization and performing low-energy modification, the problems of scale inhibitor waste and environmental pollution in the existing technology are solved, and the excellent anti-scale performance and environmental pollution of the superhydrophobic surface coating are achieved. stability.
Patent Information
- Application Number
- CN202211171938.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The prior art has problems of scale inhibitor waste and environmental pollution in preventing inorganic salt scale in metal pipes. At the same time, the scale inhibition performance of superhydrophobic surfaces is limited by structure and low surface energy substances.
An aluminum oxide nanotube layer is prepared by anodizing, and a scale inhibitor is introduced into it to form a micro-nano structure with a scale inhibitor. After low-energy modification, a superhydrophobic surface coating with excellent anti-scale properties is obtained.
It achieves long-lasting and stable anti-scaling performance, reduces the waste of anti-scaling agents and environmental pollution, has good high temperature resistance, oxidation resistance, and chlorine resistance stability, and has good dispersion in circulating water with high turbidity and high iron content.
Smart Images

Figure CN115852378B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method of a hydrophobic aluminum oxide nanoporous coating with added antiscalant and its application, belonging to the technical field of metal material surface modification. Background Art
[0002] In industrial production, many fluid media contain inorganic salts such as calcium carbonate, calcium sulfate, and barium sulfate, which are deposited on the inner surface of metal pipes and eventually form scale. In the petroleum industry, heat exchange equipment, evaporation equipment and other related industries, scaling can cause equipment and infrastructure failures, causing pipeline damage and economic losses. Therefore, various scale prevention technologies and methods have been developed, most of which use additives in fluid media, such as scale inhibitors, calcium deposit agents, and chelating agents. Although scale inhibitors are mixed with the transmission medium to prevent Mg 2+ and Ba 2+ Isocations and CO3 2- 、SO4 2- The combination of anions and other substances effectively prevents scale, but the additives are easily carried away by the fluid, causing serious waste and environmental pollution.
[0003] Due to its ultra-low adhesion, some insoluble salts are difficult to attach and grow on the surface of super-hydrophobic aluminum alloy. Therefore, the use of super-hydrophobic surfaces in industrial pipelines can effectively reduce scaling, reduce economic losses and improve the safety of industrial production. However, due to the long-term transportation of liquid media on super-hydrophobic surfaces, some hydrophobic surfaces will fail.
[0004] The inventors of the present application have found that although some metal-based super-hydrophobic surfaces have suitable rough structures and low surface energy substances can inhibit the deposition and growth of calcium carbonate salts on the surface, the scale inhibition performance of the super-hydrophobic surface is greatly limited due to the limited structure and the stability of the combination of low surface energy substances and the surface; at the same time, the scale inhibitors added to many transport liquid media only partially exert their scale inhibition performance, and most scale inhibitors will be discharged with the transport medium, causing waste and environmental pollution. Summary of the invention
[0005] In order to solve the above problems, a method for preparing a hydrophobic alumina nanoporous coating with added scale inhibitors and its application are provided. The scale inhibitors are introduced into the alumina nanotube layer prepared by anodization to form a micro-nano structure with the scale inhibitors. After low-energy modification, a super-hydrophobic surface coating with excellent anti-scaling performance can be obtained, with a contact angle greater than 150° and a rolling angle less than 10°.
[0006] According to one aspect of the present application, a method for preparing a hydrophobic alumina nanoporous coating with an antiscalant added thereto is provided, comprising the following steps:
[0007] (1) Pretreatment of aluminum alloy substrate: polish the aluminum alloy substrate to make it smooth, clean it with ultrasonic wave and then dry it;
[0008] (2) Anodizing: The aluminum alloy substrate and the graphite sheet are placed in an electrolyte, with the aluminum alloy as the anode and the graphite sheet as the cathode, and ultrasonic anodizing treatment is performed;
[0009] (3) Introduction of scale inhibitor: The aluminum alloy substrate after anodizing treatment is placed in the scale inhibitor solution, taken out after ultrasonic treatment, and kept warm in vacuum;
[0010] (4) Low-energy modification: soaking the aluminum alloy substrate obtained in step (3) in a low-energy modification solution, taking it out and vacuum drying it to obtain the hydrophobic aluminum oxide nanoporous coating with added scale inhibitor;
[0011] The scale inhibitor solution is 2-phosphonobutane-1,2,4-tricarboxylic acid solution.
[0012] Optionally, the ultrasonic parameters in step (1) are an ultrasonic power of 100 W and an ultrasonic frequency of 40 kHz, and the ultrasonic parameters in step (3) are an ultrasonic power of 100 W and an ultrasonic frequency of 40 kHz.
[0013] Optionally, in step (1), the aluminum alloy substrate is polished smooth using 2500# water-abrasive sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 10-20 minutes.
[0014] Preferably, the cleaning temperature is 25°C and the cleaning time is 15 minutes.
[0015] Optionally, in step (2), the anodization time is 15-25 min, the temperature is 10-30° C., and the current density is 15-25 A / dm 2 , ultrasonic power is 100W and ultrasonic frequency is 40kHz.
[0016] Preferably, the anodization time is 20 min, the temperature is 15°C, and the current density is 22.5 A / dm 2 .
[0017] Optionally, the electrolyte in step (2) is an oxalic acid solution, and the concentration of oxalic acid is 10-50 g / L.
[0018] Preferably, the oxalic acid is oxalic acid dihydrate, and the oxalic acid concentration is 27 g / L.
[0019] Optionally, after the ultrasonic oxidation treatment in step (2), the aluminum alloy substrate is rinsed with water and placed in an oven to dry at 120° C. for 60 minutes.
[0020] Optionally, the concentration of the 2-phosphonobutane-1,2,4-tricarboxylic acid solution in step (3) is 1-10%.
[0021] Preferably, the preparation method of 2-phosphonobutane-1,2,4-tricarboxylic acid solution is to adjust the concentration of 2-phosphonobutane-1,2,4-tricarboxylic acid solution of 20% to 1-10%.
[0022] Optionally, in step (3), the scale inhibitor is introduced for 15 minutes and vacuum dried for 30 minutes.
[0023] Optionally, the low-energy modification liquid in step (4) is an anhydrous ethanol solution of stearic acid with a concentration of 10-50 g / L.
[0024] Optionally, in step (4), the soaking time is 4-20 hours and the temperature is 20-60°C.
[0025] Preferably, the low surface energy modification time is 12 h.
[0026] According to another aspect of the present application, the application of the coating prepared by the method for preparing the hydrophobic alumina nanoporous coating with added scale inhibitor in anti-scaling of metal surfaces is also disclosed.
[0027] In this application, "room temperature" refers to 25°C.
[0028] The beneficial effects of this application include but are not limited to:
[0029] 1. According to the preparation method of the hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, the aluminum alloy substrate is first subjected to ultrasonic anodizing treatment to form a nanotubular structured alumina layer on the anode surface, giving the metal surface an anchoring space and hydrophobic properties, and then the scale inhibitor is ultrasonically introduced into the nanotubes to make it stably combined with the nanotubes to play a synergistic scale inhibition role, thereby making the coating have long-lasting and stable anti-scaling performance.
[0030] 2. According to the preparation method of the hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, by limiting the anodizing parameters, using 2-phosphonobutane-1,2,4-tricarboxylic acid solution as a scale inhibitor and ultrasonically introducing it, the prepared alumina nanotubes have excellent mechanical properties, can effectively fix the scale inhibitor and protect the substances in the tube, and can slowly release the scale inhibitor anchored in the nanotubes, thereby continuously hindering the deposition of insoluble salts in the pipeline and reducing scaling.
[0031] 3. According to the preparation method of the hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, by using 2-phosphonobutane-1,2,4-tricarboxylic acid solution as a scale inhibitor and ultrasonically introducing it, the coating has good performance in inhibiting calcium carbonate and calcium phosphate scale, good high temperature resistance, oxidation resistance, and chlorine resistance stability; at the same time, it has good dispersibility in circulating water with high turbidity and high iron; its scale inhibition performance is excellent at high temperature, and the specific phosphate group can make the additive more stably combined with the alumina surface, and the formed coating not only has scale inhibition performance but also has certain corrosion inhibition performance.
[0032] 4. According to the preparation method of the hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, by limiting the current density range, the scale inhibitors are stored in the nanotubes, and the scale inhibitors can be slowly released to inhibit scale, thereby achieving the stability and durability of the synergistic scale inhibition of the super hydrophobic surface and the scale inhibitor.
[0033] 5. According to the preparation method of the hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, the super hydrophobic surface coating prepared in the present application and the scale inhibitor in the nanostructure can both inhibit scale. The combination of the two overcomes instability and pollution respectively. After combination, the scale inhibitor is stored in the microstructure of the super hydrophobic coating, which can not only protect the scale inhibitor from flowing away with the liquid but also achieve the effect of slow release. The scale inhibitor can also continue to act on the super hydrophobic surface. The two work together to inhibit and prevent scale, overcome instability, and avoid causing a lot of environmental pollution.
[0034] 6. According to the method for preparing a hydrophobic alumina nanoporous coating with added scale inhibitors of the present application, the surface of the prepared super hydrophobic coating has an air film of a certain thickness, which further hinders the corrosion of the substrate by corrosive ions and increases the corrosion resistance of the substrate.
[0035] 7. The method for preparing the hydrophobic alumina nanoporous coating with added scale inhibitor according to the present application is simple to operate, requires simple equipment, has low preparation cost, high success rate, has no special requirements for the shape of the substrate sample, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0037] Figure 1 This is a SEM image (20 μm) of the super-hydrophobic Al2O3 nanoporous coating of Example 1 of the present invention;
[0038] Figure 2 This is an EDS image of the super-hydrophobic Al2O3 nanoporous coating of Example 1 of the present invention;
[0039] Figure 3 is a contact angle diagram of a water drop on the super-hydrophobic Al2O3 nanoporous coating prepared in Example 1;
[0040] Figure 4 This is a SEM image (20 μm) of the coating prepared in Comparative Example 2 of the present invention;
[0041] Figure 5 This is a SEM image (5 μm) of the coating prepared in Comparative Example 3 of the present invention;
[0042] Figure 6 This is the SEM image of the common aluminum alloy matrix sample after being placed for 12 hours;
[0043] Figure 7 This is the SEM image of the common aluminum alloy matrix sample after being placed for 24 hours;
[0044] Figure 8 This is the SEM image of the aluminum alloy sample with the comparative coating 1# after being placed for 12 hours;
[0045] Fig. 9 This is the SEM image of the aluminum alloy sample with the comparative coating 1# after being placed for 24 hours;
[0046] Fig.10 This is the SEM image of the aluminum alloy sample with coating 1# after being placed for 12 hours;
[0047] Fig.11 This is the SEM image of the aluminum alloy sample with coating 1# after being placed for 24 hours. DETAILED DESCRIPTION
[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0049] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0050] In step (2) of the embodiment of the present application, anodization is carried out by ultrasonic treatment in an ultrasonic pool, and the parameters of the ultrasonic pool are: power of 100 W, ultrasonic frequency of 40 kHz, and capacity of 3 L.
[0051] Example 1 Coating 1#
[0052] The preparation method of coating 1# comprises the following steps:
[0053] (1) 1060 aluminum alloy (20×20×5 mm) was selected as the substrate sample and graphite sheet (20×50×5 mm) was selected as the electrode sample. The processed 1060 aluminum alloy was polished smooth with 2500# water-abrasive sandpaper, and the polished sample was placed in anhydrous ethanol and ultrasonicated at 25°C for 15 min to remove grease and contaminants on the sample surface.
[0054] (2) The treated 1060 aluminum alloy sample and graphite sheet sample were placed in a 27 g / L oxalic acid electrolyte for anodizing treatment, with the aluminum sample as the anode and the graphite sheet as the cathode. The anodizing time was 20 min, the temperature was 15 °C, and the current density was 22.5 A / dm 2 After the reaction is finished, rinse the sample with clean water, put it in a 120℃ oven for 60 minutes, and then take out the sample for use;
[0055] (3) placing the dried anodized aluminum alloy sample in a 5% 2-phosphonobutane-1,2,4-tricarboxylic acid solution and ultrasonicating for 15 minutes, taking out the sample, and then placing the sample in a vacuum oven at room temperature and drying it for 30 minutes;
[0056] (4) The sample was placed in a 10 g / L stearic acid anhydrous ethanol solution and soaked for 12 hours; the sample was then taken out and dried in a vacuum oven at 40° C. to obtain a hydrophobic alumina nanoporous coating 1# with added scale inhibitor.
[0057] like Figure 1 As shown in the figure, the surface of the aluminum substrate of coating 1# has a regularly arranged honeycomb nanopore structure, and it can be observed that most of the pores are filled with scale inhibitors, and there is also a certain amount of scale inhibitors on the surface. Figure 2 As shown, the P content in EDS is 0.59%. Since the scale inhibitor 2-phosphonobutane-1,2,4-tricarboxylic acid contains P element, it also shows that the scale inhibitor exists in the nanopore structure of the aluminum matrix; for the high content of C and O elements, on the one hand, the surface-modified stearic acid contains a large amount of C and O elements, and on the other hand, the scale inhibitor 2-phosphonobutane-1,2,4-tricarboxylic acid also contains a large amount of C and O elements, which also proves that the scale inhibitor exists in the alumina nanotube structure.
[0058] The contact angle test results are as follows: Figure 3 As shown, the static contact angle of a 4 μL water droplet on the hydrophobic alumina nanoporous coating 1# with antiscalant added was measured by a contact angle meter to be 155°.
[0059] Example 2 Coating 2#
[0060] The preparation method of coating 2# comprises the following steps:
[0061] (1) 1060 aluminum alloy (20×20×5 mm) was selected as the substrate sample and graphite sheet (20×50×5 mm) was selected as the electrode sample. The processed 1060 aluminum alloy was polished smooth with 2500# water-abrasive sandpaper, and the polished sample was placed in anhydrous ethanol and ultrasonicated at 25°C for 10 min to remove grease and contaminants on the sample surface.
[0062] (2) The treated 1060 aluminum alloy sample and graphite sheet sample were placed in a 10 g / L oxalic acid electrolyte for anodizing treatment, with the aluminum sample as the anode and the graphite sheet as the cathode. The anodizing time was 15 min, the temperature was 10 °C, and the current density was 15 A / dm 2 After the reaction is finished, rinse the sample with clean water, put it in a 120℃ oven for 60 minutes, and then take out the sample for use;
[0063] (3) placing the dried anodized aluminum alloy sample in a 1% 2-phosphonobutane-1,2,4-tricarboxylic acid solution and ultrasonicating for 15 minutes, taking out the sample, and then placing the sample in a vacuum oven at room temperature and drying it for 30 minutes;
[0064] (4) The sample was placed in an anhydrous ethanol solution of stearic acid with a concentration of 20 g / L and soaked for 4 hours; the sample was then taken out and dried in a vacuum oven at 20° C. to obtain a hydrophobic alumina nanoporous coating 2# with an antiscalant added thereto.
[0065] The static contact angle of a 4 μL water droplet on the hydrophobic alumina nanoporous coating 2# with antiscalant added was measured by a contact angle meter to be 151°.
[0066] Example 3 Coating 3#
[0067] The preparation method of coating 3# comprises the following steps:
[0068] (1) 1060 aluminum alloy (20×20×5 mm) was selected as the substrate sample and graphite sheet (20×50×5 mm) was selected as the electrode sample. The processed 1060 aluminum alloy was polished smooth with 2500# water-abrasive sandpaper, and the polished sample was placed in anhydrous ethanol and ultrasonicated at 25°C for 20 min to remove grease and contaminants on the sample surface;
[0069] (2) The treated 1060 aluminum alloy sample and graphite sheet sample were placed in a 50 g / L oxalic acid electrolyte for anodizing treatment, with the aluminum sample as the anode and the graphite sheet as the cathode. The anodizing time was 25 min, the temperature was 30 °C, and the current density was 25 A / dm 2 After the reaction is finished, rinse the sample with clean water, put it in a 120℃ oven for 60 minutes, and then take out the sample for use;
[0070] (3) placing the dried anodized aluminum alloy sample in a 10% 2-phosphonobutane-1,2,4-tricarboxylic acid solution and ultrasonicating for 15 minutes, taking out the sample, and then placing the sample in a vacuum oven at room temperature and drying it for 30 minutes;
[0071] (4) The sample was placed in a 50 g / L stearic acid anhydrous ethanol solution and soaked for 20 hours; the sample was then taken out and dried in a vacuum oven at 60° C. to obtain a hydrophobic alumina nanoporous coating 3# with an antiscalant added thereto.
[0072] The static contact angle of a 4 μL water droplet on the hydrophobic alumina nanoporous coating 3# with antiscalant added was measured by a contact angle meter to be 153°.
[0073] Comparative Example 1 Comparative Coating 1#
[0074] The difference between Comparative Example 1 and Example 1 is that the scale inhibitor 2-phosphonobutane-1,2,4-tricarboxylic acid is not introduced in Comparative Example 1, that is, step (3) is not performed in Comparative Example 1, and the other steps are the same as in Example 1.
[0075] Comparative Example 2 Comparative Coating 2#
[0076] The difference between Comparative Example 2 and Example 1 is that the current density in step (2) of Comparative Example 2 is 10 A / dm 2 , other step parameters are the same as those in Example 1.
[0077] The SEM image of the comparison coating 2# is as follows Figure 4 As shown, it can be seen that the aluminum oxide surface is not etched evenly, and there is no honeycomb structure to anchor the scale inhibitor. The static contact angle of a 4 μL water droplet on the comparison coating 2# is 123°, and the rolling angle is greater than 10°, as measured by a contact angle meter.
[0078] Comparative Example 3 Comparative Coating 3#
[0079] The difference between Comparative Example 3 and Example 1 is that the concentration of the scale inhibitor in step (3) of Comparative Example 3 is 20%, and the other step parameters are the same as those of Example 1.
[0080] The SEM image of the comparison coating 3# is as follows Figure 5 As shown, it can be seen that the honeycomb structure on the surface is covered with a large area, the scale inhibitor only exists on the surface, and the scale inhibitor is easy to lose. The static contact angle of a 4μL water droplet on the comparative coating 3# is 130° and the rolling angle is greater than 10° as measured by the contact angle meter.
[0081] Experimental example
[0082] The ordinary aluminum alloy substrate sample, the aluminum alloy sample with the comparison coating 1# and the aluminum alloy sample with the coating 1# were subjected to a static experiment of saturated calcium carbonate solution to simulate the scale-containing industrial transport fluid. Two samples of each of the three samples were placed in a beaker containing saturated calcium carbonate solution. At a temperature of 40°C, the beaker was sealed with a plastic wrap and a small hole was left to maintain the air pressure in the beaker. One sample of each sample was placed continuously for 12 hours, and the other sample was placed continuously for 24 hours. The sample was taken out, the sample surface was gently cleaned with deionized water, and the sample was dried in an oven and taken out, and the surface scaling was observed with SEM. For details, see Figure 6-Figure 11 As shown, Note: (The main crystal types of calcium carbonate are: calcite, vaterite, aragonite, and the stability of calcite is greater than that of vaterite which is greater than that of aragonite).
[0083] from Figure 6-Figure 11 It can be clearly seen that after the surface of the ordinary aluminum alloy substrate sample without any surface treatment was immersed in a saturated calcium carbonate solution for 12 hours, calcium carbonate scale began to appear on the surface; after continuous immersion for 24 hours, the Al surface was covered with a large amount of stable calcite-type calcium carbonate scale. The aluminum alloy sample with comparative coating 1# was taken out after being immersed in a saturated calcium carbonate solution for 12 hours, and the surface contact angle remained greater than 150°, and no calcium carbonate deposition was observed on the surface in SEM; after continuous immersion in a saturated calcium carbonate solution for 24 hours, calcium carbonate deposition of aragonite crystal type was observed on the surface in SEM, and the surface contact angle remained greater than 150°. After the aluminum alloy sample with coating 1# was immersed in a saturated calcium carbonate solution for 12 hours and 24 hours, no calcium carbonate deposition was observed in SEM, and the surface contact angle was still greater than 150°.
[0084] The above results show that the hydrophobic alumina nanoporous coating with added scale inhibitor has the synergistic properties of super hydrophobic scale inhibition and scale inhibitor scale inhibition, and has excellent scale inhibition performance in the industrial transportation industry.
[0085] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a hydrophobic alumina nanoporous coating with an antiscalant added, characterized in that: The following steps are involved: (1) Pretreatment of aluminum alloy substrate: polish the aluminum alloy substrate to make it smooth, clean it by ultrasonic and then dry it; (2) Anodizing: The aluminum alloy substrate and the graphite sheet are placed in an electrolyte, with the aluminum alloy as the anode and the graphite sheet as the cathode, and ultrasonic anodizing treatment is performed; (3) Introduction of scale inhibitor: Place the aluminum alloy substrate after anodizing treatment into the scale inhibitor solution, take it out after ultrasonic treatment, and keep it warm in vacuum; (4) Low-energy modification: the aluminum alloy substrate obtained in step (3) is immersed in a low-energy modification solution, taken out and then vacuum dried to obtain the hydrophobic aluminum oxide nanoporous coating with added scale inhibitor; Wherein, the scale inhibitor solution is 2-phosphonobutane-1,2,4-tricarboxylic acid solution; The temperature of the anodizing in step (2) is 10-30°C and the current density is 15-25A / dm 2 ; In step (2), the anodization time is 15-25 min, the ultrasonic power is 100 W, and the ultrasonic frequency is 40 kHz; in step (2), the electrolyte is an oxalic acid solution, and the concentration of oxalic acid is 10-50 g / L; The concentration of the 2-phosphonobutane-1,2,4-tricarboxylic acid solution in step (3) is 1-10%; the ultrasonic parameters in step (3) are ultrasonic power of 100 W and ultrasonic frequency of 40 kHz.
2. The preparation method according to claim 1, characterized in that: In step (1), the aluminum alloy substrate is polished smooth using 2500# water-abrasive sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 10-20 minutes.
3. The preparation method according to claim 1, characterized in that: After the ultrasonic oxidation treatment in step (2), the aluminum alloy substrate is rinsed with water and placed in an oven to dry at 120° C. for 60 minutes.
4. The preparation method according to claim 1, characterized in that: In step (3), the scale inhibitor is introduced for 15 minutes and vacuum dried for 30 minutes.
5. The preparation method according to claim 1, characterized in that: In step (4), the low-energy modification liquid is an anhydrous ethanol solution of stearic acid with a concentration of 10-50 g / L.
6. The preparation method according to claim 1, characterized in that: In step (4), the soaking time is 4-20 hours and the temperature is 20-60°C.
7. Use of a coating prepared by the method for preparing a hydrophobic alumina nanoporous coating with added scale inhibitor as claimed in any one of claims 1 to 6 in anti-scaling of metal surfaces.